Evolution of interface character distribution in duplex stainless steel processed by cross-rolling and annealing. Issue 11 (November 2018) - Wang, Ming; Xu, Ting; Zhu, Yanli; Yin, Wenhong; Guo, Hong; Zhao, Ertuan; Fang, Xiaoying; Wang, Weiguo
Abstract: Duplex stainless steel UNS S31803 samples were cross-rolled with a true strain of ε = 2 followed by annealing at 1323 K for 2 min and 240 min, respectively. The distributions of intervariant boundary planes in the precipitated austenite (A) from ferrite (F) and phase boundary planes conforming to Kurdjumov-Sache (K-S) orientation relationship (OR) were characterized by electron backscatter diffraction (EBSD) and the five-parameter analysis (FPA) method, respectively. The intervariant boundary planes with misorientation angle of 60° around <111> and <011> occur frequently and tend to terminate on the 111 plane. At the grain size level of 4 μm, the phase boundary appears to be connected with the K-S OR terminating on 110F ‖111A at the early stage of annealing. When the grain size reaches approximately 20 μm, phase boundary was modified into 541F ‖533A due to twinning in austenite during annealing.